KOORDINASI PEMERINTAH KOTA DALAM UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOTIKA DI KOTA PEKANBARU - Yuhandi, Randi; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research present describe the coordinations of government city toward prenetive of narchotics smuggling in Pekanbaru city. The increase of narchotics users in Pekanbaru city in this years are very dangerous and make a Pekanbaru city as a city in Riau Province that have a high cases. Most of people that use a narchotics are young generations. Then this case have been a attention from the government of Pekanbaru city.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Padangsidimpuan city and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of National Narchotics Agency of Riau Province, Head of National Narchotics Agency of Pekanbaru city, Health Agency of Pekanbaru and Social Education of Pekanbaru city.The research shows that coordinations of government city toward prenetive of narchotics smuggling in Pekanbaru city have done by two ways of coordinations that is vertical coordinations are cooperation held by Pekanbaru Government with group society, schools institutions in Pekanbaru and GRANAT institutions. In order that the horizontal coordinations are held by Pekanbaru Government with National Narchotics Agency and Education, Health Agency. Some factors that influence of coordinations are weakness of law system and supremacy of law, the decrease of society awareness and culture society that not care about the dangerous of narchotics in Pekanbaru city.Keywords: coordinations, government, prevention and narchotics